The Danish National badminton center: A successful talent development environment - Larsen, C. H.; Storm, L. K.; Henriksen, K. (14th World Congress of Sport Society Psychology, 2017)
A specific shared feature of the successful environments is a strong and coherent organizational culture characterized by a close coherence between espoused and enacted values. Organizational culture of elite and talent development environments and sporting organizations exerts an important impact on athlete development and performance. Limited research attention has been paid to factors associated with optimal organizational functioning or excellence in sport (Wagstaff, Fletcher, & Hanton, 2012). This is problematic since factors such as organizational climate and culture have an impact on performance all the way to the Olympic level (Gould & Greenleaf, 2002; Gould & Quinan 2002) and Fletcher and Wagstaff (2009) asserts that a "twilight zone" exists regarding how individuals and the team interact with the broader organization. This study was organized as an explorative integrative and qualitatively oriented case study. Methods of data collection included interviewing coaches, young players, professional players, management, and also observations of daily life in the center to obtain systematic and detailed knowledge of the environment as it occurs in the real world. The environment was characterized by a strong relationship between players and a community of coaches and the performance director. A learning environment focused on developing intelligent, self aware and dedicated players. The environment had a strong organizational culture that was based on proximal role models, openness, collaboration despite being competitors and a learning community between players and coaches. These characteristics were perceived as essential for success in the environment and related to performance of the athletes.